Use of Advanced Numerical Methods for the Strength Prediction of Peel-dominated Bonded Joints - J. T. S. Xara; R. D. S. G. Campilho (New Trends in Physical Science Research Vol. 3, 2022)
The application of adhesive bonding to composite structures supposes the existence of reliable design tools to accurately analyse the joints’ behaviour. In this context, the eXtended Finite Element Method (XFEM) is a relatively new method for predicting the fracture behaviour of bonded’ joints. The goal of this research is to investigate single-L adhesive joints between aluminium components and carbon-epoxy composites under peeling stresses using XFEM, taking into account variations in the thickness of the L-shaped adherend \((t_P 2)\) and adhesives of different ductility. For damage initiation, the XFEM analysis used stress or strain criteria, as well as multiple damage law types for fracture propagation. Experimentation was used to validate the results. The XFEM analysis revealed that this method is very accurate when using the stress-based quadratic initiation criterion and the triangular propagation law.